Macroeconomic impact of public debt and foreign aid in Sri Lanka - Maitra, Biswajit (369 EGFR SIGNALING IMPAIRS THE ANTIVIRAL ACTIVITY OF INTERFERON-ALPHA, 2019)
Accumulation of public debt in Sri Lanka is raised significantly since the independence. It exceeded 100% of gross domestic products (GDP) in the late 1980s and the early 2000s. Although it has been declined in the recent past and becomes 79.3% of GDP in 2016; the high level of debt in a weak fiscal position of the small economy Sri Lanka is an issue of concern. In this backdrop, this paper examines the impact of public debt and foreign aid on income, price level and interest rate in Sri Lanka for the post-reform period. It is found that public debt in general and foreign debt, in particular, depresses income and stimulates price level. Domestic debt has some impact on the price level. On the other hand, foreign aid has a deleterious effect on both the income and price level. The foreign debt and aid have raised interest rate both in the short-run and in the long-run, while no significant impact of the domestic debt on interest rate is found. Based on these findings, the paper elaborates on some long-term measures for reducing the dependence on debt and aid in Sri Lanka.